EXPERIENŢA REALIZĂRII APLICAŢIILOR ORIENTATE LA UTILIZATOR - Căpățână, Gheorghe (CEP USM, 2007)
During the transition period from the existing technologies to new ones based on a different philosophy, all methods regarding information system design are welcome if they are capable to be immediately exploited and modified by the final users.
Keywords: sisteme informaționale